Reproduction, growth, survival and carcass composition of two strains and reciprocal crosses of nile tilapia, Oreochromis niloticus (Linnaeus, 1757) - Avillanosa, Augustus P. (1999)
Two F1 Nile tilapia strains and their reciprocal crosses were evaluated for their seed production in this study. The two Nile tilapia strains were : the Nile Zarraga (NZ) strain and the Genetically Improved Farmed Tilapia (GIFT). The experimental treatments consisted of Trt I (NZ female x NZ male) ; Trt II (GIFT female x NZ male), Trt III (NZ female x GIFT male) ; and Trt IV (GIFT female x GIFT male). After 14 days of breeding in hapa at a stocking density of 224.1 to 261.0 g/m3, results showed that seed production was influenced by strain. The highest seed production was obtained by intra-strain cross Trt I at 4,568 seed/kg female and was significantly (P.0.05) different from Trt IV with 2, 110 seed/kg female. However, TRT I did not significantly differ from inter-strain cross Trt II with 3,265 seed/kg female.The F2 of two strains and their reciprocal crosses were evaluated for their growth, survival and carcass com[position comparing the normal and methyltestosterone (MT)-treatments. The fry (0.01g) of all crosses were given no hormone feed for normal treatments and with methyltestoosterone hormone feed for MT-treatments for 28 days. For the normal treatment there were four treatments, Trt IA, IIA, IIIA and IVA, while in the MT-treatments there were also four treatments, Trt IB, IIB, IIIB and IVB. All treatments were subjected to thr consecutive rearing experimental phases: sex reversal treatments (SRT), nursery and grow-out phases. In the SRT phase, fry stocked at 100 pcs/m3 in hapa for 28 days rearing and in the nursery phase, fingerlings stocked at 250 pcs/m3 for 49 days of rearing, showed no effect of strain and hormone on fry growth. In the grow-out phase, wherein fish were stocked at 50 pcs/m3 reared for 57 days in cages, comparing Trt IIA within normal treatments, Trt IIA obtained significantly (P,0.01) higher mean weight (105.53 g) over other normla treatments. Trt IIB obtained higher mean weight (146.23 g) and total production (7.31 kg/m3) which were significantly (P,0.01) different from the other MT-treatments indicating the advantage of maternal contribution of the GIFT strain. Carcass traits (dressed and filleted weights) of Trt IV (GIFT female x GIFT male) was highest in both normal and MT-treatments. In the proximate composition, protein, fat fiber and ash content, no differences were found in all treatments. The inter-strain cross GIFT female x NZ male in Trt II and hormone treating their fry gave bettr growth i the grow-out phase than other treatments. This also indicated that maternal effect and hormone treatment improved fish growth in the grow-out phase, but not in the early rearing phases (SRT and nursery phases). This further showd thatthere is improvement on the fish growth at the grow-out phase in the MT-treatments as compared to the normal treatments because the MT-treatments had high percentage (91.5 to 93.5%) of male.
Thesis--(M. S. Fisheries-Aquaculture)--College of Fisheries and Oceanology, U. P. in the Visayas, April 2005.
Keywords: Nile tilapia; reochromis niloticus (Linnaeus, 1757).